Highly efficient and stable tandem organic light-emitting devices based on HAT-CN/HAT-CN:TAPC/TAPC as a charge generation layer. Issue 26 (9th June 2015) - Dai, Yanfeng; Zhang, Hongmei; Zhang, Zhiqiang; Liu, Yipeng; Chen, Jiangshan; Ma, Dongge
Abstract : We demonstrated an effective charge-generation layer (CGL) composition consisting of three layers: an organic acceptor material HAT-CN, HAT-CN blended with an organic donor material TAPC and TAPC, to fabricate a high efficiency tandem organic light-emitting diode (OLED). Abstract : We demonstrated an effective charge-generation layer (CGL) composition consisting of three layers: an organic acceptor material 1, 4, 5, 8, 9, 11-hexaazatriphenylene hexacarbonitrile (HAT-CN), HAT-CN blended with an organic donor material 4, 4′-cyclohexylidenebis[ N, N -bis(4-methylphenyl)benzenamine] (TAPC) and TAPC, to fabricate a high efficiency tandem organic light-emitting diode (OLED). The utilization of the HAT-CN: TAPC blending layer between HAT-CN and TAPC in a CGL greatly enhances charge generation and separation, which was found by carrying out current–voltage analyses. This means that the three-layer structure is more suitable as a connecting unit for the fabrication of high efficiency tandem OLEDs. Clearly, the tandem OLEDs based on HAT-CN/HAT-CN:TAPC/TAPC as CGL showed more than double enhancement in current efficiency with respect to the corresponding single-unit device, which is also higher than that of tandem OLEDs with HAT-CN/TAPC as CGL. More encouragingly, the power efficiency of tandem OLEDs with the new CGL was enhanced by about 1.3–1.5 times, reaching 113 lm W −1 at 1000 cd m −2 brightness as compared to 76 lm W −1 from the single-unit OLEDs and 86 lm W −1 from the HAT-CN/TAPC-based tandem OLEDs. The tandem OLEDs with the new CGL also showed good stability, at least enhancing 4.5 times compared with the single unit devices. Furthermore, three-unit tandem OLEDs based on this new CGL were also fabricated. The maximum current efficiency reached 286 cd A −1 and was maintained at 266 cd A −1 at a luminance of 10 000 cd m −2 .